2006
DOI: 10.1096/fj.06-5885fje
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic activity of human chorionic gonadotropin through LH receptor activation on endothelial and epithelial cells of the endometrium

Abstract: Successful embryo development requires an extensive endometrial angiogenesis in proximity of implantation site. The glycoprotein hCG is produced even before implantation by trophoblast in normal pregnancy. In this manuscript, we demonstrate an angiogenic effect of hCG in several in vivo (chick chorioallantoïc membrane, matrigel plug assay, aortic ring assay) and in vitro experimental models. In contrast, human placental lactogen (hPL) did not display angiogenic properties. LH/hCG receptor was detected in endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 57 publications
3
108
0
1
Order By: Relevance
“…We applied three models of angiogenesis, which have been previously successfully used to evaluate the contribution of different metalloproteinases during angiogenic processes (Masson et al, 2002;Berndt et al, 2006Berndt et al, , 2008. The transplantation system is a highly sensitive tool to inspect the kinetic of early steps of host stromal response to tumor signals (Mueller and Fusenig, 2004;Jost et al, 2007Jost et al, , 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied three models of angiogenesis, which have been previously successfully used to evaluate the contribution of different metalloproteinases during angiogenic processes (Masson et al, 2002;Berndt et al, 2006Berndt et al, , 2008. The transplantation system is a highly sensitive tool to inspect the kinetic of early steps of host stromal response to tumor signals (Mueller and Fusenig, 2004;Jost et al, 2007Jost et al, , 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Matrigel (500 ml) containing heparin (10 U/ml) and bFGF (250 ng/ml) were injected subcutaneously into mice (n ¼ 16). To quantify functional vessel recruitment, hemoglobin concentrations were measured in the plugs harvested 7 days after injection (Berndt et al, 2006). The angiogenic response induced by bFGF was again higher …”
Section: Resultsmentioning
confidence: 99%
“…This could suggest a more complicated relationship, with LH directly involved in the pathogenesis of IHD, perhaps mediated via the LH receptor (LHR). Although originally thought to be present only in gonadal cells, the LHR has since been identified in extragonadal sites (44), including smooth muscle and vascular tissue (45,46). Berndt et al (45) reported that the expression of LHR was associated with endothelial cell proliferation in the mouse aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally thought to be present only in gonadal cells, the LHR has since been identified in extragonadal sites (44), including smooth muscle and vascular tissue (45,46). Berndt et al (45) reported that the expression of LHR was associated with endothelial cell proliferation in the mouse aorta. LH might therefore theoretically exert a direct effect on the heart or associated vascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocyst hCG increases endometrial secretion of proimplantatory leukaemia inhibitory factor (LIF; Perrier d' Hauterive et al 2004) and macrophage-colony stimulating factor (M-CSF; Licht et al 2001), increases stromal COX2 (cyclo-oxygenase 2) expression (Han et al 1996) and reduces the expression of the decidual marker IGF-BP1 (insulinlike growth factor binding protein 1) during the late secretory phase (Licht et al 2002;Fluhr et al 2006). Blastocyst hCG also increases the production of vascular endothelium growth factor (VEGF) by the endometrial epithelium and stimulates endometrial angiogenesis, suggesting that hCG actively participates in placental development (Zygmunt et al 2002;Berndt et al 2006). Finally, the fetal allograft contributes to its tolerance by the competent maternal immune system via the FAS-FAS ligand pro-apoptosis system (Kayisli et al 2003), its inhibitory actions on endometrial interleukin (IL)-6 (Perrier d' Hauterive et al 2004) and complement C3 and C4 factors (Sherwin et al 2007) and by stimulating maternal regulatory T cells (Zenclussen et al 2006).…”
Section: Introductionmentioning
confidence: 99%